An Uncommon Case of Bilateral Breast Enlargement Diagnosed as Tumoral Pseudoangiomatous Stromal Hyperplasia: Imaging and Pathological Findings - Isabel Sollozo-Dupont; Héctor Alejandro Domínguez-Hernández; Cecilia Pavón-Hernández; Yolanda Villaseñor-Navarro; Robin Shaw-Dulin; Victor Manuel Pérez-Sánchez; Alejandro Javier España-Ferrufino; Laura Marysol Álvarez-Guadarrama; Fany Iris Porras-Reyes; M. Patricia Pérez-Badillo (Case Reports in Radiology)
The incidence of reported pseudoangiomatous stromal hyperplasia (PASH), as well as the variability and severity of clinical presentations, is increasing in the literature. In parallel, several authors posit the need for an improved classification of PASH to avoid possible variables associated with this diagnosis. Here, we present a 25-year-old woman with PASH accompanied by severe bilateral and symmetrical breasts enlargement, highlighting an uncommon clinical presentation of PASH as much as the careful interdisciplinary review and correlation of histology and all available imaging studies to confirm the definitive diagnosis.